2010
DOI: 10.1007/s12080-010-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-organised spatial patterns and chaos in a ratio-dependent predator–prey system

Abstract: Mechanisms and scenarios of pattern formation in predator-prey systems have been a focus of many studies recently as they are thought to mimic the processes of ecological patterning in real-world ecosystems. Considerable work has been done with regards to both Turing and non-Turing patterns where the latter often appears to be chaotic. In particular, spatiotemporal chaos remains a controversial issue as it can have important implications for population dynamics. Most of the results, however, were obtained in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
98
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 53 publications
3
98
1
Order By: Relevance
“…This feature of our model can be in part explained by observing that it displays interesting dynamics in the spatially uniform case since the physically relevant steady state can lose its stability via a transcritical bifurcation as well as via a supercritical Hopf bifurcation. This latter circumstance seems to be noteworthy because recent studies [2,3] have shown that the emergence of spatio-temporal patterns in reaction-diffusion systems can be related to the presence of unstable homogeneous states, like those found beyond a supercritical Hopf bifurcation.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…This feature of our model can be in part explained by observing that it displays interesting dynamics in the spatially uniform case since the physically relevant steady state can lose its stability via a transcritical bifurcation as well as via a supercritical Hopf bifurcation. This latter circumstance seems to be noteworthy because recent studies [2,3] have shown that the emergence of spatio-temporal patterns in reaction-diffusion systems can be related to the presence of unstable homogeneous states, like those found beyond a supercritical Hopf bifurcation.…”
Section: Introductionmentioning
confidence: 93%
“…The coupling between these two kinds of instabilities was first theoretically investigated in the 90's in the framework of the Lengyel-Epstein model of the CIMA reaction [56]. Since then it has become a key topic for pattern formation in the reaction-diffusion framework and has been extensively investigated in chemistry, physics and biology [2,3,24,33,48,49,55].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pattern formation for two species model [11][12][13][14][16][17][18][19]] based on coupled reaction diffusion equations has been intensively investigated. The necessary and sufficient condition for Turing instability, which leads to the formation of spatial patterns, has been derived [9,16,17,20] and very interesting patterns are also obtained from the numerical simulation results [9,21,22].…”
Section: Introductionmentioning
confidence: 99%